Rapid Administration of Methoxyflurane to Patients in the Emergency Department (RAMPED) Study: A Randomized Controlled Trial of Methoxyflurane Versus Standard Care. (28th October 2020) - Brichko, Lisa; Gaddam, Ravali; Roman, Cristina; O'Reilly, Gerard; Luckhoff, Carl; Jennings, Paul; Smit, De Villiers; Cameron, Peter; Mitra, Biswadev
Abstract: Objective: The objective was to evaluate the effectiveness of methoxyflurane versus standard care for the initial management of severe pain among adult emergency department (ED) patients. Methods: This randomized parallel‐group open‐label phase IV trial of methoxyflurane was conducted in a tertiary hospital ED setting in Australia. Inclusion criteria required adult patients to have an initial pain score ≥ 8 on the 11‐point Numerical Rating Scale (NRS). Patients were randomized 1:1 to receive either inhaled methoxyflurane (3 mL) or standard analgesic treatment at ED triage. The primary outcome was the proportion of patients achieving clinically substantial pain reduction, defined as a ≥50% drop in the pain score at 30 minutes. Secondary outcomes included the pain score at multiple time points (15, 30, 60, 90 minutes) and the difference in the proportion of patients achieving a >2‐point reduction on the NRS. Results: There were 120 patients randomized and analyzed between September 4, 2019, and January 16, 2020. The primary outcome was achieved in six (10%) patients in the methoxyflurane arm and three (5%) in the standard care arm (p = 0.49). A higher proportion of patients in the methoxyflurane arm reported a >2‐point drop on the NRS at all time points (17% vs. 5% at 15 minutes, 25% vs. 9% at 30 minutes, 30% vs. 10% at 60 minutes, and 33% vs. 13% at 90 minutes). Methoxyflurane use was also associated with lower median pain scores at all time points. Conclusion: Initial management with inhaled methoxyflurane in the ED did not achieve the prespecified substantial reduction in pain, but was associated with clinically significant lower pain scores compared to standard therapy.